Rutin prevents EqHV-8 induced infection and oxidative stress via Nrf2/HO-1 signaling pathway - Chen, Li; Li, Shuwen; Li, Wenjing; Yu, Yue; Sun, Qi; Chen, Wenjing; Zhou, Huaqi; Wang, Changfa; Li, Liangliang; Xu, Meng; Khan, Muhammad Zahoor; Li, Yubao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The Nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway has been extensively studied for its role in regulating antioxidant and antiviral responses. The Equid herpesvirus type 8 (EqHV-8) poses a significant threat to the equine industry, primarily manifesting as respiratory disease, abortions, and neurological disorders in horses and donkeys. Oxidative stress is considered a key factor associated with pathogenesis of EqHV-8 infection. Unfortunately, there is currently a dearth of therapeutic interventions available for the effective control of EqHV-8. Rutin has been well documented for its antioxidant and antiviral potential. In current study we focused on the evaluation of Rutin as a potential therapeutic agent against EqHV-8 infection. Methods For this purpose, we encompassed both in-vitro and in-vivo investigations to assess the effectiveness of Rutin in combatting EqHV-8 infection. Results and Discussion The results obtained from in vitro experiments demonstrated that Rutin exerted a pronounced inhibitory effect on EqHV-8 at multiple stages of the viral life cycle. Through meticulous experimentation, we elucidated that Rutin’s antiviral action against EqHV-8 is intricately linked to the Nrf2/HO-1 signaling pathway-mediated antioxidant response. Activation of this pathway by Rutin was found to significantly impede EqHV-8 replication, thereby diminishing the viral load. This mechanistic insight not only enhances our understanding of the antiviral potential of Rutin but also highlights the significance of antioxidant stress responses in combating EqHV-8 infection. To complement our in vitro findings, we conducted in vivo studies employing a mouse model. These experiments revealed that Rutin administration resulted in a substantial reduction in EqHV-8 infection within the lungs of the mice, underscoring the compound’s therapeutic promise in vivo. Conclusion In summation, our finding showed that Rutin holds promise as a novel and effective therapeutic agent for the prevention and control of EqHV-8 infections.